Psycho- Social Adjustment and its Relationship to Self-Esteem among Adolescents Residing in Protection and Care Homes in Amman - Jordan - Abdallah Almahaireh; Rania Omar (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to investigate the level of psycho-social adjustment and self-esteem among  adolescents residing in the protection and care homes in Amman-Jordan, to discover the relationship between psycho-social adjustment and self-esteem. The sample of the study consisted of (137) adolescents (96 males and 41 females) from protection and care homes in Amman, aged between 12-16 years. To achieve the aims of the study, two scales were developed: a psycho-social adjustment scale and a self-esteem scale. Validity and reliability of the scales were verified. The results showed that the level of psycho-social adjustment and self-esteem among adolescents residing in the protection and care homes in Amman-Jordan was medium. There was a statistically significant positive correlation between psycho-social adjustment and self-esteem. Moreover, the results showed that there was a statistically significant difference in levels of psycho-social adjustment and self-esteem due to gender in favor of females.